103. Multi-site experiences of radiation dose index monitoring (RDMI) in interventional radiology (IR) and cardiology. (December 2018) - Isoardi, P.; D'Ercole, L.; Pini, S.; Delle Canne, S.; Del Vecchio, A.; Di Liberto, R.; Ghetti, C.; Gianusso, L.; Giordano, C.; Paruccini, N.; Pasquino, M.; Quattrocchi, M.; et al.
Abstract : Purpose: The Council Directive 2013/59/EURATOM considers IR to be a special practice involving high doses and requiring strict monitoring to ensure the best quality assurance programs. This work reports the early experience of managing dose data of angiographic patients in a multicenter study. Methods: The project has involved a sample of about 10000 procedures gathered from twelve Italian hospitals centers involved on voluntary basis. The survey concerned the collection of data related to different IR procedures: interventional cardiology, radiology, neuroradiology, vascular surgery, Urology, Endoscopy and Pain Therapy from mobile and fixed units. The analysis includes 24 procedure and for each exam, air-kerma, kerma-area product and fluoroscopy time were collected. In few centres data collection was made with the aid of automatic DACS systems. For others, data were collected and processed manually. Results: Duration and complexity of fluoroscopic exposures for each procedure are strongly dependent on the individual clinical circumstances, the observed distribution of patient doses is very wide, even for a specified protocol. The fixed radiological machines, all with Flat Panel, are of four different brands: Philips, Siemens, Toshiba and GE; C-arm are Siemens, Philips and Eurocolumbus. The median values of the parameters were compared with the LDRs proposed at Italian level for some procedures (GISE, INAIL, ISS) or at international level. For other procedures without LDRs, this work is a first attempt to propose LDR values also in the light of the ICRP 135. Conclusions: This first data collection serves to take stock of the situation on patient's dosimetry in several sectors and is the starting point for obtaining any LDRs recalling that, these latter, are dependent on the state of practice and the available technology at a particular point in time. A certain degree of patient dose reduction can be achieved without affecting image quality adversely.